2010
DOI: 10.1068/i0389
|View full text |Cite
|
Sign up to set email alerts
|

Pioneers of Eye Movement Research

Abstract: Recent advances in the technology affording eye movement recordings carry the risk of neglecting past achievements. Without the assistance of this modern armoury, great strides were made in describing the ways the eyes move. For Aristotle the fundamental features of eye movements were binocular, and he described the combined functions of the eyes. This was later given support using simple procedures like placing a finger over the eyelid of the closed eye and culminated in Hering's law of equal innervation. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
38
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 58 publications
1
38
0
8
Order By: Relevance
“…It was improved by Shackel in 1960 [4], and then in 1962 by Mackworth and Thomas [5]. In 1967, Yarbus [1] started the research using his oculometer, and thus, opened a wide, new field of research. The era of modern eyetracking began in the 1970s with the studies performed by Young and Sheena and their successors [6].…”
Section: Types Of Eye Movementsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was improved by Shackel in 1960 [4], and then in 1962 by Mackworth and Thomas [5]. In 1967, Yarbus [1] started the research using his oculometer, and thus, opened a wide, new field of research. The era of modern eyetracking began in the 1970s with the studies performed by Young and Sheena and their successors [6].…”
Section: Types Of Eye Movementsmentioning
confidence: 99%
“…Research on visual reading strategy started in the 1930s [1]. In 1931, Earl and Taylor developed 2 devices, called "Ophthalmograph" and "Metronoscope," that enable accurate recording of eye movements, and above all, of saccades and fixations [1]. The 1st "eye-tracker" (a device for recording eye movements) in a form of a helmet equipped with a mini-camera was the work of Hartridge and Thompson (1948) [3].…”
Section: Types Of Eye Movementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The direct relationship between the functional integrity of the brain and corresponding eye movements makes testing of oculomotor behavior a potential tool to allow for objective measures and inferences on brain integrity postconcussion. 3 Given that concussion can disrupt multiple brain functional networks, including the oculomotor control networks, our previous study focused on the acute effects of concussion by having participants perform a battery of oculomotor tests while simultaneously undergoing fMRI. Behavioral results revealed that concussed participants performed worse in all oculomotor tasks and had increased fMRI recruitment and larger areas of activation.…”
mentioning
confidence: 99%
“…When the face assumes one apparent direction, the eyes accompany the face, and it is not immediately evident from which portrait the eyes are retained. Even earlier, dynamic aspects of eye movements to signal expression were commented upon by Wells (1792), an authority on vision and one of the pioneers of eye movement research (see Wade 2000Wade , 2010. He wrote: " The whole variety, then, of the expressions of feeling which are justly attributed to the eye, must, I think, depend upon its motions.…”
mentioning
confidence: 99%